The Effect of Halal Lifestyle on Economic Growth in Indonesia - Novalini Jailani; Hendri Hermawan Adinugraha (Universitas Muhammadiyah Yogyakarta, 2022)
The halal lifestyle has become a trend for the global community and Indonesia, which incidentally has a Muslim majority population. The total expenditure spent by the Indonesians on halal products in 2017 was USD 218.8 billion. It can be stated that halal product is such a good business, especially in Indonesia. For this reason, this study aims to determine whether the halal lifestyle, Islamic banking, halal tourism, and halal food sector could increase Indonesia's economic growth. Several sources, such as books, articles, journals, and journal papers, were used for this paper. This study found that the halal lifestyle in the sharia banking, halal tourism, and halal food sector positively affected Indonesia's economic growth.